Effects of Incorporation of Marble Powder Obtained by Recycling Waste Sludge and Limestone Powder on Rheology, Compressive Strength, and Durability of Self-Compacting Concrete - Rayed Alyousef; Omrane Benjeddou; Chokri Soussi; Mohamed Amine Khadimallah; Abdeliazim Mustafa Mohamed (Advances in Materials Science and Engineering)
Marble has been commonly used as a building material since ancient times. The disposal of waste materials from the marble industry, consisting of sludge that is composed of powder mixed with water, is one of the current worldwide environmental problems. This experimental study aims to valorize marble powder, which is achieved by grinding the sludge as filler added to the cementitious matrix of self-compacting concrete (SCC). The main purpose of this work is to evaluate the marble filler effects on the rheology in the fresh state and on the hardened properties of SCCs compared to those of limestone filler. To this end, two SCCs, SCCM and SCCL, manufactured using marble powder and limestone filler, respectively, were prepared and tested. The fresh properties of the two SCCs’ mixtures were determined by slump flow, L-box, V-funnel, sieve stability, bulk density, and air content. Tests on hardened SCCs included compressive strength, homogeneity, and quality in terms of ultrasonic pulse velocity and durability against carbonation and water penetration. In addition, scanning electron microscope (SEM) and X-ray diffraction (XRD) were used to analyze the specimens.